Peran Guru dalam Menanamkan Nilai Demokrasi Bagi Siswa melalui Mata Pelajaran Pendidikan Kewarganegaraan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the role of teachers, the obstacles faced, and the role of teachers in overcoming these obstacles in instilling democratic values through Civics Education (PKn) subjects for students of SMP Negeri 4 Tuhemberua. Democratic values such as freedom of opinion, tolerance, deliberation, and responsibility are an important part in shaping students' character to become good citizens. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers have a strategic role in instilling democratic values, both through the learning process in the classroom and through extracurricular activities. Teachers act as facilitators, motivators, and role models in fostering democratic attitudes in students. Obstacles faced include the lack of active student participation and limited learning media, but these can be overcome with a creative and participatory approach. Thus, Civics learning makes a significant contribution in shaping students' democratic attitudes and behavior in the school environment. Furthermore, in the learning process in the classroom, teachers use various active methods such as group discussions, deliberation simulations, and debates that aim to encourage students to get used to expressing opinions responsibly. Teachers also frequently relate material to current social phenomena, enabling students to see the relevance of democratic values in everyday life. Furthermore, teachers instill the values of tolerance and respect for differences through concrete examples and everyday behaviors both inside and outside the classroom. Another obstacle identified in this study was the students' diverse social backgrounds, which influenced their perspectives on democratic values. Some students still struggled to understand the importance of respecting others' opinions or were not yet accustomed to playing openly.